Carrier's liability for marine pollution under Indonesian maritime law - Maruf, Irma Rachmawati (2017)
This study analyses the high risk nature of Indonesian waters and the safety of ships crossing these waters in the aspect of liability. Since the country lies across continents and oceans, such vulnerable areas tend to cause ship accidents. The government has undertaken revision of relevant regulations and the upgrading of facilities of transportation in its effort to minimize shipping accidents. Data from the Ministry of Transportation of Indonesia showed the trend of ship accidents has increased between 2009 until 2014. The objectives of the study therefore are to examine the principle of liability in Indonesian law; to determine which law could be applied in relation to marine pollution; to examine the pattern of sea pollution that ships had caused; and analyze the mechanism of compensation for ships that has been involved in eradicating the pollution caused by such shipping accidents based on Shipping Law Number 11 of 2008. This study focuses on marine pollution caused by ships involved in accidents and incidences at Indonesian sea. The method of research is to make a legal analysis of the key provisions of relevant laws upon the liability of parties in shipping accidents. Interviews were conducted with the experts in the field of marine pollution such as judges, ministerial officers of Ministry of Transportation and Maritime Court including shipping companies. The findings indicated that there are various forms of carrier’s liability in Indonesia namely the principle of fault liability regulated in Indonesian Commercial Code, liability based on negligence adopted by Shipping Law Number 11 of 2008 and the strict liability principle adopted in Indonesian Environmental Law 2007. Currently, the principle of strict liability could be applicable in the case of marine pollution although in some cases in court, the judges still apply the fault liability principle. The finding from the case laws and authority has also indicated that, strict liability is not a new law in Indonesia but still facing difficulties in its implementation and application. In the quest for suitable solution, the principle of mutual liability can be added as a new legal principle to assist the application of the principle of strict liability. It is also found that the legal framework as basis for the application of mutual liability principle in Indonesia is already relevant in existing laws.